Analysis of natural circulation frictional resistance characteristics in rod bundle channel. (May 2019) - Zhang, Yinxing; Gao, Puzhen; Kinnison, W. Wayne; Ji, Peng; Zhou, Jian; Lin, Yuqi
Highlights: This study presents experimental studies of the single-phase resistance. Study of resistance characteristics in rod bundles under low Reynolds number. An improved correlation of the frictional resistance coefficient is obtained. Introduce kinematic viscosity correction factor for correction. This newly developed correlation predicts data with a relative error within ±5%. Abstract: A considerable amount of research has gone into understanding the thermal-hydraulics characteristics of rod bundle channels which is of great importance for the nuclear industry. This paper will show that the development of the correlation of the frictional resistance coefficient in rod bundle channels under natural circulation conditions is well understood. This paper presents experimental studies of the single-phase resistance and obtains an improved correlation of the frictional resistance coefficient under natural circulation conditions based upon thermal-hydraulics characteristics which are well understood. It is also shown that this newly developed correlation closely predicts data. The experimental results show that the frictional resistance coefficient of a rod bundle channel under natural circulation is related to the physical properties of fluid and the size of the rod bundle channel. According to different flow regions, the relationship between the frictional resistance coefficient and Reynolds number is discussed separately, and the expressions of frictional resistance coefficient with Reynolds number in laminar flow region and transition region are obtained. After considering the influence of fluid properties on the frictional resistance coefficient, this paper introduces the kinematic viscosity correction factor to correct the frictional resistance coefficient. Finally, the complete expression of the frictional resistance coefficient was obtained. This newly developed predictive expression is in good agreement with experimental data in both the laminar and transition flow regions, with a relative error within ±5%. Thus we now have a predictor of the frictional resistance coefficient under natural circulation conditions based upon more complete thermal-hydraulic parameters in a static state.